Transformasi Digitalisasi UMKM Fashion di Bandung tahun 2000 – 2022 - Vito Taufiq Hidayat; Carolina Santi Muji Utami (Historia, 2027)
This research aims to analyze digital transformation in the fashion Micro, Small and Medium Enterprises (MSME) sector in the city of Bandung over a period of two decades (2000-2022). As the center of the national textile industry, Bandung is experiencing fundamental changes in the distribution and marketing patterns of fashion products. Using historical research methods, this article traces the transition of offline sales dominance in industrial and retail centers towards digital technology. Research findings show that the implementation of mobile banking (m-banking) is the main foundation that changes transaction behavior, which is then strengthened by the role of e-commerce platforms as an important role during the transition period. The Covid-19 pandemic was identified as a disruptive factor that paradoxically had a positive impact in the form of accelerating the digital ecosystem for fashion MSMEs to survive in the global market.